Unity in diversity? Polarization, issue diversity and satisfaction with democracy. Issue 12 (1st December 2020) - Hoerner, Julian M.; Hobolt, Sara B.
ABSTRACT: How do the range of issues voters care about and party system polarization impact democratic outcomes? Recent debates have focused on the negative effect of polarized systems on democratic quality. However, the extent to which this polarization is channeled or diffused over a wide range of issues on the public agenda has not been analyzed systematically. Using data from 31 European countries from 2003 to 2018, we show that party polarization indeed has a negative effect on people's satisfaction with democracy. Importantly, however, we demonstrate that at high levels of issue diversity, the negative effect of polarization is minimized. Drawing on the deliberative democracy literature, we argue that at low levels of issue diversity, polarization makes compromise in society less likely and the political discourse more antagonistic. However, at higher levels of issue diversity, contestation and conflict can be diffused over a large range of issues, providing more favorable conditions for collective will formation and, ultimately, higher levels of satisfaction with democracy.